Synchrotron micro-computed tomography unveils the three-dimensional structure and origin of staminodes in the Plains Prickly Pear Cactus Opuntia polyacantha Haw. (Cactaceae) - Cota-Sánchez, J. Hugo; Falconer, Denver J.; de Almeida, Odair J. G. [UNESP]; Stobbs, Jarvis A.; Vera-Vélez, Roy; Rice, Ryan S.; Belliveau, Nicholas A. (Springer Nature, 2023)
Floral appendages display an array of shapes and sizes. Among these organs, staminodes are morphologically diverse structures that have lost the ability to produce pollen, but in some instances, they produce fertile pollen grains. In the family Cactaceae staminodes are uncommon and range from simple linear to flat to spatulate structures, but studies describing their structural attributes are scanty. This study highlights the advantages of synchrotron radiation for sample preparation and as a research tool for plant biology. It describes the internal morphology of floral parts, particularly stamen, tepal, and staminode in the Plains Prickly Pear Cactus, Opuntia polyacantha, using synchrotron radiation micro-computed tomography (SR-μCT). It also shows the different anatomical features in reconstructed three-dimensional imaging of reproductive parts and discuss the advantages of the segmentation method to detect and characterize the configuration and intricate patterns of vascular networks and associated structures of tepal and androecial parts applying SR-μCT. This powerful technology led to substantial improvements in terms of resolution allowing a more comprehensive understanding of the anatomical organization underlying the vasculature of floral parts and inception of staminodes in O. polyacantha. Tepal and androecial parts have uniseriate epidermis enclosing loose mesophyll with mucilage secretory ducts, lumen, and scattered vascular bundles. Cryptic underlying structural attributes provide evidence of a vascularized pseudo-anther conjoint with tepals. The undefined contours of staminodial appendages (pseudo-anther) amalgamated to the tepals’ blurred boundaries suggest that staminodes originate from tepals, a developmental pattern supporting the fading border model of floral organ identity for angiosperms.
Keywords: Computed tomography; Pseudo-anther; Stamen; Staminode; Synchrotron; Tepaloid staminode